Les Normes du travail - Verge, Pierre (Relations industrielles / Industrial Relations, 1993)
The article reviews the book, "Les Normes du travail," by Jean-Louis Dubé and Nicola D'Iorio.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor law; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z